Cover Image. Issue 9 (5th September 2021) - Unknown
Abstract : COVER PHOTO: Bottlenose dolphins ( Tursiops truncatus ) produce individually identifiable calls called signature whistles. Using underwater acoustic recorders off the coast of Maryland, USA, in the Atlantic Ocean and Chesapeake Bay, Bailey et al. ( Ecosphere, Volume 12, Issue 8, Article e03685; https://doi.org/10.1002/ecs2.3685 ) found a total of 1518 unique signature whistles. This indicates the minimum number of dolphins that occurred within the study area during 2016–2018. There were reoccurrences of the same signature whistles across years and sites, indicating site fidelity as well as movement of bottlenose dolphins between the Chesapeake Bay and the Atlantic coast off Maryland. These results can help inform management of this protected species. Photo credit: Melissa McCeney.